Os processos de (des)(re)territorialização dos ex-moradores do bairro Santa Felicidade : uma intervenção urbana a partir do PAC - Gonçalves, Julia Silva (2016)
The Organizational Studies have been insterting themes as space and territory in its discussions, specially when the objective leads to public and social matters, and with critic reflexion focusing on the realation among social actors. Cities have been dealt with in diferente ways for Administration scholars, it started with the management approach, for its complexity and also for the many different ways of organizing cities. This research dealt with the cities thematic and saw its deepness and complexity, through different angles, as an organization and its neighborhoods as territories, meaning appropriate spaces in concrete or symbolic ways. Social dynamics requires economia, social, politics and cultural actions, often lead by the State, privileged holder of intervention power. In 2007 the Brazilian Federal Government proposed the Growth Aceleration Programme - PAC, with the economic purpose of investing in large infrastructure projects. Among those, the requalification of urban areas projects, one of which took place in Maringá-PR, the city where this research was held, the requalification project of Santa Felicidade neighborhood, proposed the increase of land and streets enlargement, this new disposal had as consequence the relocation of one third of the families, they had to move to many other neighborhoods in the city, two of those were the territories where this study took place: Honorato Veccchi and Odwaldo Bueno Netto. The families relocation and other processes which happened and continue happening were seen through territorial thematic, along with the deterritorialization and reterritorialization processes, dealing with the exit of people and their trials of readaptation, difficulties and the existing subjectivities in this processes. Some of the families from Santa Felicidade are living the multiterritoriality proposed by Haesbaert, when the destruction and creation of territories happen at the same time as well as their deterritorialization and reterritorialization. Another point treated on this research is the segregation which take place in brazilian cities, in Maringá, this characteristics has been part of the city´s history since the begining, this situation makes it easier to observe the public power and its partnership with private initiative, ignoring the needs of population, favoring real estate sector and not the public policies objectives. The territorial phenomenon continue happening in the cities, making its studies possible, and favoring deeper discussions and researches on this theme, dealing with public politics, its functions and the needs of population, left out of the discussion most of the time. This is a qualitative research, the data were analyzed using Gil Flore´s interpretation technique and the result brought the difficulty of people when trying to adapt in new neighborhoods, their affective tie with the old neighborhood, and their worries with legal documents of their new places. The respondents have shown their regreat of moving, and how much they miss their old neighbors, their habits, but, when dealing with the cultural importance of having a place to live, they seem satisfied, another important point is the difference between deterritorialization of rich and poor people, the poor have no choice of moving, and no option of going or not when they deal with people who have money and political power.